LC‐HRMS/MS study of the prodrug ciclesonide and its active metabolite desisobutyryl‐ciclesonide in plasma after an inhalative administration to horses for doping control purposes. Issue 2 (30th October 2021) - Trevisiol, Stéphane; Moulard, Yves; Kaabia, Zied; Delcourt, Vivian; Loup, Benoit; Garcia, Patrice; Boyer, Sophie; Dauriac, Karine; Groseille, Guillaume; Rouger, Sébastien; Narbe, Ruediger; Popot, Marie‐Agnès; et al.
Abstract: Ciclesonide (CIC) is the first inhaled highly potent corticosteroid that does not cause any cortisol suppression. It has been developed for the treatment of asthma in human and more recently in equine. CIC is the active compound of Aservo® EquiHaler® (Boehringer Ingelheim Vetmedica GmbH), the pre‐filled inhaler generating a medicated mist based on Soft Mist™ technology. This prodrug is rapidly converted to desisobutyryl‐ciclesonide (des‐CIC), the main pharmacologically active compound. Due to its anti‐inflammatory properties, CIC is prohibited for use in horse competitions. To set up an appropriate control, the determination of detection times and screening limits are required. Therefore, a highly sensitive analytical method based on supported liquid extraction (SLE) combined with liquid chromatography–high resolution tandem mass spectrometry (LC‐HRMS/MS) was developed to detect CIC and its active metabolite des‐CIC in plasma. The lower limit of detection of CIC and des‐CIC was approximately 1 pg/ml in plasma. After a pilot study conducted on a single horse at the recommended dose (eight actuations twice daily corresponding to 5.5 mg/day for the first 5 days, followed by 12 actuations once daily corresponding to 4.1 mg/day in the last 5 days), the same protocol was applied in the main study using six horses. In all horses, CIC and des‐CIC levels were less than 5 and 10 pg/ml, respectively, at 36 h after the end of the administration. The outcome of this risk assessment study should be useful to draw any recommendations for horse competitions. Abstract : This study shows the kinetic elimination study of the prodrug ciclesonide and its active metabolite desisobutyryl‐ciclesonide in horse plasma after an inhalative administration for doping control purposes.